Wprowadzenie dyktatury wojskowej w wyniku zamachu stanu a kwestia międzynarodowego uznania rządu na przykładzie przewrotu wojskowego w Mjanmie z 1 lutego 2021 roku - Gajos, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article reflects on the question of recognizing a government in international law in relation to the coup that took place in Myanmar on 1 February 2021. First, the author defines the recognition of a government, emphasizing that the institution of recognition applies exclusively to unconstitutional changes of governments. The circumstances of the coup in Myanmar are recounted, exhibiting that the authoritarian regime of the junta has been established in a manifest violation of provisions established in the Constitution adopted in 2008. Second, the competing criteria for recognition of a government in international law are discussed with reference to Tobar (favoring legitimacy) and Estrada doctrines (according to which effectiveness shall prevail). The author presents the evolution of opinions in scholarship and in the practice of states that occurred over the course of decades and led to the dominance of the latter concept. It is demonstrated that upon the application of the criterium of effectiveness with regard to the junta in Myanmar, it should be recognized as a body entitled to represent the state. Finally, acknowledging the tendency that originated in the 1990s to take into account the democratic norm as an alternative basis for recognition of a government or its denial, the author claims that in the lack of coherent and uniform state practice in that field, such a norm cannot create a normative obligation as a norm of customary international law, and therefore does not justify nonrecognition of junta.
Keywords: Mjanma; junta; Tatmadaw; zamach stanu; uznanie rządu